Link performance analysis of Unmanned Aerial Vehicles - Oishi, Aniqa Tasnim; Rahman, Leeyana Ferheen; Siddika, Mosarrat Jahan; Arnab, Shahriar (BRAC University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.